Características ecofisiológicas de crambe em condições de estresse hídrico - Boiago, Nayara Parisoto (2012)
The seeds produced by Crambe abyssinica Hochst (crambe) species have great potential in the biodiesel industry that currently searches for new sources of biomass to reach its production goals. As this culture species is rarely developed, it is essential to carry out researches on ecophysiological behavior to implement it in the Brazilian energy matrix. In order to characterize the ecophysiological behavior of crambe, this study evaluated the growth and allelopathic potential of crambe under conditions of water stress in two stages. vi Crambe plants were submitted to different levels (4, 8, 12, 16 and 20 days) of irrigation cancelation during the vegetative and flowering stages. At each level, the following parameters were analyzed: number of leaves, plants heights, leaf area and total dry weight and calculated physiological indexes of leaf area ratio (LAR), specific leaf area (SLA), net assimilation rate (NAR) and relative growth rate (RGR), all analyzed by linear exponential regression. In addition, it was carried out a leaf constitution analysis of micro and macronutrients by atomic absorption spectrophotometry. The static aqueous extract was prepared from its shoots to evaluate the allelopathic potential of crambe under water stress, at 2 and 4% concentration and then added to Petri dishes with 25 seeds of lettuce for each one. Experiments were carried out in a germination chamber with distilled water and osmotic potential (PEG 6000) as control treatments, based on a completely randomized design. The obtained data were percentage (%G) and germination speed index (GSI), root (RL) and shoot lengths (SL) of seedlings and averages were compared by Tukey test at 5% significance level. Crambe plants showed some decrease on leaf area and total dry matter in the vegetative stage, in the last level of stress. For the same developmental stage, an effect of water stress was observed at LAR, SLA, NAR and RGR indexes, concluding that this stage of development is more sensitive to drought effects. The extracts that were prepared at 4% concentration showed higher allelopathic effects. During vegetative development, there was a decrease in allelopathic potential of plants along the stress, but, during flowering, crambe plants affected negatively germination and seedling initial development of lettuce during the 4th and 16th days of water stress. Thus, it was concluded that the cancelation of irrigation on crambe plants differed in terms of development period and intensity of water stress